CHANGES IN CRITICAL THINKING SKILLS AND DISPOSITIONS ASSOCIATED WITH THE IMPLEMENTATION OF A BLENDED CURRICULUM IN THREE COURSES OF A VETERINARY MEDICINE PROGRAMME - Payan-Carreira, Rita; Sacau, Ana; Ferreira, David; Rebelo, Hugo; Sebastião, Luis (IATED Academy, 2025)
This paper reports on the implementation and evaluation of critical thinking (CT) blended curricula in three courses of a Veterinary Medicine Programme, as part of the Think4Jobs Project (https://think4jobs.uowm.gr/). The project aimed to foster CT development through discipline-specific interventions and assess their impact on students' CT skills and dispositions. During the 2022/23 academic year, three courses piloted these curricula: Imaging – diagnostic image analysis and problem-solving; Deontology – ethical dilemma analysis and professional decision-making; Andrology, Gynecology and Obstetrics – clinical case analysis and diagnostic reasoning. Pre- and post-intervention assessments were conducted using validated tools: the Critical Thinking Self-Assessment Scale’ Short Form (CTSAS-SF) and the Student-Educator Negotiated Critical Thinking Dispositions Scale (SENCTDS). Analysis of responses (n=100) showed significant gains in all CT skills dimensions (p≤0.0001) and in overall CT dispositions (p=0.010), particularly Reflection (p=0.001), Perseverance (p=0.005), and Intrinsic Goal Motivation (p≤0.0001). However, Attentiveness, Organization, and Open-mindedness showed no significant change. No significant differences emerged between the courses, indicating that intentional pedagogical design fostering CT is more relevant than the specific course content or discipline. These findings support the integration of blended CT curricula across veterinary education and emphasize the role of constructivist learning strategies in developing both reasoning skills and reflective dispositions critical for professional practice.
Keywords: Critical Thinking; Blended Curriculum; Veterinary Education; Constructivist Learning; Educational Innovation